Optical repeater for indoor visible light communication using amplify-forward method - Arsyad Ramadhan Darlis; Lucia Jambola; Lita Lidyawati; Adisty Hanny Asri (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper, the implementation of an optical repeater for indoor visible light communication using the amplify-forward method was proposed. In indoor, visible light communication (VLC) can occur by transmitting information signals from lamps as a VLC transmitter toward the VLC receiver as line-of-sight (LOS) that is located with only a few meters. In the non-los (NLOS) communication, the signal will be attenuated, so it needs to amplify to improve good signal quality in a VLC receiver. The optical repeater could be used to improve the signal quality that attenuating due to distance. The audio signal was generated and sent using VLC Transmitter toward the light emitting diode (LED). Then, the electrical signal was converted to become visible light, and it was amplified using an optical amplifier with an amplify-forward method. The signal in the form of visible light that had been amplified would be received by the photodiode (PD), and the VLC receiver processed it. The measurement results showed the system that used the optical repeater could improving the distance until 9.5 m with frequency 6000 Hz, where the best signal quality at a frequency of 3000 Hz. The measurement result showed that the use of repeater components with the amplify-forward method for VLC systems, especially in the room, can increase the range until 4.5 m compare without an optical repeater. This result exceeds the minimum distance of an indoor visible light communication system, with an average distance of the roof to the floor is 3.5 m.